Resolution of Land Rights in Forest Areas Reviewed from Agrarian Law - Wijayanti, Diah (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
Indonesia, as a state governed by the rule of law, mandates that all legal issues be regulated through statutory provisions to ensure clarity and compliance by its citizens. The registration of land within Forest Areas presents distinct legal and administrative complexities compared to general land registration processes. A recurrent conflict arises from the fact that communities residing in Forest Areas often lack formal land certificates, which serve as the highest legal proof of land ownership. This research aims to identify viable legal solutions enabling communities residing within Forest Areas to obtain land certificates in accordance with prevailing statutory provisions. Employing a normative juridical method, this study integrates statutory and conceptual approaches, supported by an analysis of relevant legislation, scholarly literature, and scientific journals. The findings reveal that communities within Forest Areas may secure land certificates through a collective application submitted via the mayor or regent, following the procedural requirements stipulated in Presidential Regulation No. 88 of 2017 concerning the Settlement of Land Tenure in Forest Areas. Upon issuance of a ministerial decree by the Minister of Environment and Forestry adjusting the boundaries of the Forest Area in compliance with applicable laws, the National Land Agency is authorized to issue the corresponding land certificates. This study offers a legal framework that bridges statutory requirements and practical implementation, potentially contributing to the resolution of long-standing land tenure disputes in Forest Areas.